The Influence of Non-Performing Loans on the Profitability of Nepal’s National Level Development Bank - Dahal, Suraj; Gurung, Rajesh; Dahal, Rewan Kumar; Ghimire, Binod (Nepalese Journal of Management Science and Research, 2024)
The objective of this research is to evaluate the influence of non-performing loans on the profitability of Development banks in Nepal. To test the research hypothesis, secondary data were obtained from multiple sources, such as Banking and Financial Statistics, Bank Supervision Reports issued by the Nepal Rastra Bank, and annual reports of banks. In addition, descriptive and casual comparative research design method was used to analyze sample data of a total of 8 development banks operating at the national level. The findings of the study can help development banks to refine their risk management strategies.